A graft copolymer of collagen hydrolysate obtained from chrome leather scraps for retardation in Portland cement. (15th February 2021) - Ding, Xiaoliang; Ye, Bo; Dai, Rui; Chen, Hui; Shan, Zhihua
Abstract: The effective use of chrome leather scraps not only addresses the issue of properly disposing of leather waste but also can produce added-value products. In this paper, collagen hydrolysate (CH) from chrome leather scraps was modified by graft copolymerization using acrylic acid and acrylamide to synthesize grafted CH (GCH), and then for the first time used for retardation in Portland cement. FTIR analysis showed that the CO stretching vibration peak of GCH at 1685 cm −1 was obviously appeared compared with that of CH, which indicated that graft copolymerization between CH and the monomers successfully occurred. The GCH exhibited excellent stability and biodegradability. The addition of GCH efficiently postponed the setting process of the cement. The strength of the cement was closely linked to the dosage of GCH. The addition of 0.1% GCH improved the strength of the cement, but the addition of more than 0.1% GCH caused a decline in the strength. SEM observation showed that the crystal morphology of the cement significantly changed from needle-like to lumpy with the addition of GCH. Moreover, we also found that the hydration reaction of cement reactants (such as alite and belite) was inhibited and less hydration product (Ca(OH)2 ) was formed after the addition of grafted CH, thereby achieving the retarding effect. This paper indicated that GCH can be used as a novel and eco-friendly cement retarder, providing a path for maximizing the recycling of leather waste and achieving sustainable development in the leather industry. Highlights: Leather waste was used to prepared cement retarder for the first time. The grafted CH had satisfying retardation on the cement. The grafted CH changed the crystal morphology of cement. The grafted CH inhibited the hydration process of cement reactants and formation of hydration products.